Sharia Maqashid-Based Zakat Management At Laz (Amil Zakat Institution) Al-Bunyan Bogor City - Mulauddin, Aforisma; Agustin, Ratna Nur (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
Zakat Management is a process related to managerial activities in Zakat so that the funds collected in Zakat can be managed and distributed properly to the parties who are entitled to receive it. The purpose of this study is to determine the management of Zakat Management at LAZ Al-Bunyan Bogor City, To determine the supporting and inhibiting factors of zakat management at LAZ Al-Bunyan Bogor City and to know the efforts of LAZ Al-Bunyan in Risk Management of Zakat Management. This research uses qualitative research methods with primary data collection methods in the form of interviews and secondary data from books, journals and relevant articles on the discussion of Zakat Management which is processed based on the observations of researchers in the field. The Work Program of LAZ Al-Bunyan carrying Maqashid Shari'ah includes: Programs to safeguard Religion, Programs to safeguard the Soul, Programs to safeguard Intellect, Programs to safeguard offspring, and Programs to safeguard Property. The supporting factor for zakat management at LAZ Al-Bunyan is the trust of the community, while the inhibiting factor is that zakat literacy is still relatively low. Preverentive steps or efforts to get out when facing problems (risk management) is one of them with the level of supervision. Management of Zakat Management at LAZ Al-Bunyan Bogor City in its application is appropriate and complete as Management Theory contains Planning, Organizing, Implementing, and Supervising.